Impact of verbal and web-based patient education programs driven by clinical pharmacist on the adherence and illness perception of hypertensive patients - OKUYAN, BETÜL; SANCAR, MESUT; YEŞİLDAĞ, OSMAN (Association of Pharmaceutical Teachers of India, 2020)
Background: Patient education is a substantial factor for the management of inveterate diseases. The aim of this study is to assess the impact of patient education given by clinical pharmacist using different (verbal and web-based) education techniques on the adherence and illness perception of hypertensive patients. Methods: It is a prospective observational study. Patients selected were randomly assigned to 2 groups: Verbal Based Education Group (VBEG) and Web Based Education Group (WBEG). Patients’ adherence and hypertension illness perception were measured using “Medication adherence selfefficacy scale-short form (MASES-SF)” and “Illness Perception Questionnaire-revised (IPQ-R)” at the baseline meeting. 1 month after baseline meeting, patient education was given to patients and 4 months after patient education, the questionnaires were repeated. The scores were evaluated and statistically analyzed. Results: Of the 120 patients (60 VBEG and 60 WBEG) available for total follow-up at 5 months, after patient education total score of Medication adherence self-efficacy scale-short form increased in both groups. The cumulative percentage change in statistically significant questions was found to be higher in WBEG (62,3%) than in the VBEG (40,4%). After education mean scores of the 7 subscales of illness representation part of IPQ-R were significantly increased in both groups (p<0,05). The cumulative percentage change for five subscales was found to be higher in WBEG (38,8%) than in the VBEG (26,7%). Conclusion: Our study shows that patient education has positive effect both on patient adherence and hypertension illness perception of hypertensive patients, regardless of education technique. This study had also shown that WBE had similar positive effects with VBE when driven by clinical pharmacist. © 2020, Association of Pharmaceutical Teachers of India. All rights reserved.
Keywords: Adherence; Hypertension; Illness perception; Knowledge; Patient education; Web-based Education